Redefining Education for Gen Z: Heutagogy, Internships, and Collective Efforts Toward a Resilient Future - Carolyn F Hall (Educational Considerations, 2025)
As Gen Z enters an era of rapid technological change, economic uncertainty, and global challenges, traditional education models must evolve to foster adaptability, autonomy, and resilience. This article explores the role of heutagogy (self-determined learning), internships, and collective action in redefining education to prepare students for an unpredictable future. By shifting from passive knowledge acquisition to learner-driven exploration, integrating real-world experience through internships, and fostering collaborative problem solving, education can empower Gen Z with the critical thinking, creativity, and resilience needed to thrive.
Keywords: heutagogy; internships; resilience